AKULTURASI BUDAYA PADA POLA PERMUKIMAN TRADISIONAL DI KAMPUNG GANTARANG LALANG BATA KABUPATEN KEPULAUAN SELAYAR - Wasilah Sahabuddin; Fadhil Surur (Diponegoro University, 2018)
The process of communication and interaction between indigenous peoples and the outside community gives birth to a distinctive form of cultural acculturation. The process also occurs in traditional communities in Gantarang Lalang Bata. As the center of the kingdom, they have been interacting with people with different cultures between Java, Malay, and Europeans. The purpose of this research is to study the form of cultural acculturation that influences the development. Data collection technique is done through primary data and secondary data. The analytical technique used is descriptive analysis by constructing reality and cultural meaning and approach of a sense of place. The results showed that the pattern of settlement Gantarang Lalang Bata formed an association between human elements and natural elements. Different cultural diversity systems between Hindus, Javanese, Europeans, and Arabs have an influence on the formation of landscapes. Cultural style of Hindu that leads to the tradition of pakammik, the Javanese element refers to the mosque building, the existence of the cannon as an attribute of European elements and tradition and layout associated with Arabic influence. The influence of Javanese culture - Islam became the most dominant side influenced settlement pattern and formed mekka keke as a sense of place from the old village of Gantarang Lalang Bata.